Torque Performance of Optimally Designed Multi-Phase Reluctance DC Machines - Rakgati, Edward Tshitshiri (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Electric and Electronic Engineering))--University of Stellenbosch, 2006.